2020
DOI: 10.2196/20317
|View full text |Cite
|
Sign up to set email alerts
|

Design and Usability Evaluation of Mobile Voice-Added Food Reporting for Elderly People: Randomized Controlled Trial

Abstract: Background Advances in voice technology have raised new possibilities for apps related to daily health maintenance. However, the usability of such technologies for older users remains unclear and requires further investigation. Objective We designed and evaluated two innovative mobile voice-added apps for food intake reporting, namely voice-only reporting (VOR) and voice-button reporting (VBR). Each app features a unique interactive procedure for report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…In particular, for detecting individuals with high loneliness scores, the binary-classification model using acoustic features achieved the best accuracy. Although user-interface studies reported that voice input was effective and was preferable as an input modality for older adults (94)(95)(96), other studies reported that the performance of automatic speech recognition tended to be worse in older adults than in other age groups (97,98). Because we analyzed only speech data collected in a lab setting, we may need to consider the possibility that there would be a situation where automatic speech recognition would be difficult to use for extracting linguistic features from speech data collected in living situations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for detecting individuals with high loneliness scores, the binary-classification model using acoustic features achieved the best accuracy. Although user-interface studies reported that voice input was effective and was preferable as an input modality for older adults (94)(95)(96), other studies reported that the performance of automatic speech recognition tended to be worse in older adults than in other age groups (97,98). Because we analyzed only speech data collected in a lab setting, we may need to consider the possibility that there would be a situation where automatic speech recognition would be difficult to use for extracting linguistic features from speech data collected in living situations.…”
Section: Discussionmentioning
confidence: 99%
“…the requirements of older people. This includes adaquetely adapted user interfaces [27,38], big fonts, auditory feedback [39,40], or additional input methods (i.e., voice input) which support their demands [26]. On these grounds, we developed the mHealth application called NEMO (Figure 5).…”
Section: Use Case B: Nemomentioning
confidence: 99%
“…On these grounds, we intend to discuss a comprehensive workflow on different approaches and give a perspective on possible strategies to integrate mHealth applications into clinical care routines. Our workflow addresses the main requirements of both healthcare professionals and patients (Table 1) to ensure effective and safe inter-sectorial communication [11,23,24,25,26,27,28,29]. To address these issues and address concerns from patients and healthcare professionals, one must improve the digital patient-doctor communication and relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Users are interested in core functions such as speed of running, reminders, notifications, encouragement, follow-up, goal setting, and online video presentation, and in the way they are provided [31,34,[64][65][66] Quality of information Information quality has a significant impact on older people's acceptance of intelligent health management technologies [22,67] Personalization Personalization is a key characteristic that enhances the attractiveness and acceptability of IHMT [35,41,[68][69][70][71] Interactivity Interactive games and healthcare worker or peer interactions can increase interest in older adults [5,17,26,27,45,58,62,[70][71][72] Perceived ease of use User interface design Devices with simple operation, large font, and touch screen interface are more popular [23,26,42,46,48,68,73,74] Efficiency Voice input design can improve time efficiency [75] Security…”
Section: Perceived Usefulness Functionalitymentioning
confidence: 99%
“…In terms of efficiency, the application of touch screens [42] and voice input [75] can facilitate the use by the elderly and improve the use efficiency.…”
Section: Security and Privacymentioning
confidence: 99%